Peran Informasi Perusahaan dan Perhatian Investor terhadap Initial return Saham IPO di Pasar Modal Indonesia Periode 2021-2024 - Fitria, Novita; Meidiaswati, Harlina (Seminar Nasional Manajemen, 2026)
This study aims to analyze the effects of the intended use of IPO proceeds, retail investor attention, and board gender diversity on initial returns for IPO firms during the 2021–2024 period. The intended use of IPO proceeds is measured using three components: growth opportunities, working capital, and debt repayment. This study employs a quantitative approach with purposive sampling, resulting in a sample of 188 companies. The data were analyzed using multiple linear regression with Stata version 17. The results indicate that the allocation of IPO proceeds to growth opportunities has a significant negative effect on initial return, while retail investor attention has a significant positive effect on initial return. However, the allocation of IPO proceeds to working capital and debt repayment, as well as board gender diversity, does not have a significant effect on initial return. Therefore, the allocation of IPO proceeds to growth opportunities and the level of retail investor attention should be considered in determining IPO strategy and the formation of initial return.